On the benefit of melatonin in protection against ouabain-induced arrhythmia through modulation of oxidative stress factors in isolated rat atria. Issue 5 (3rd September 2018) - Tokazzabani Belasi, Fatemeh; Vaezi, Gholamhassan; Bakhtiarian, Azam; Hojati, Vida; Mousavi, Zahra; Nikoui, Vahid
ABSTRACT: Considering the cardioprotective and antioxidant properties of melatonin, in the present experiment, we investigated the possible involvement of oxidative stress factors in antiarrhythmic effects of melatonin in ouabain-induced arrhythmia in isolated rat atria. Male rats were divided into two groups, receiving either of melatonin (2 mg/kg) or vehicle, orally once daily for three weeks. Rats were anesthetized, and atria were isolated and incubated with ouabain in an organ bath. Time of onset of arrhythmia and asystole as well as atrial beating rate and contractile force were recorded. We also measured the activity of superoxide dismutase (SOD) and levels of thiobarbituric acid reactive substances (TBARS) in atria after injection of ouabain to animals. Pretreatment of animals with melatonin could significantly postpone the onset of arrhythmia and asystole compared with vehicle-treated group ( P  ≤ 0.001). Incubation of ouabain boosted the atrial beating rate in vehicle-treated group ( P  ≤ 0.01), while this response in melatonin-treated group was not significant ( P  > 0.05). Injection of ouabain decreased the activity of SOD and increased the levels of TBARS in atria ( P  ≤ 0.001, P  ≤ 0.01, respectively), while pretreatment of animals with melatonin reversed these effects ( P  ≤ 0.05). It is concluded that melatonin possesses antiarrhythmic properties, and oxidative stress factors might mediate this response.